(untitled) (Bangladesh Journal of Botany, 2025)
This study investigates the plant communities of Juniperus phoenicea subsp. turbinata and J. oxycedrus subsp. macrocarpa in the coastal region of Tlemcen. The low number of individuals reflects strong anthropogenic degradation at both sites. Factorial correspondence analysis identified five phytoecological groups: two at Rechgoune, assigned to the Oleo-Ceratonion alliance and the Pistacio-Rhamnetalia alaterni order, and three at Marsat Ben M’hidi, related to halo-psammophilous associations and sub-associations. The biological spectrum is dominated by therophytes (16-27 species), followed by chamaephytes (0-15), hemicryptophytes (3-9), geophytes (2), and phanerophytes (2-8). These results highlight the ecological diversity, evolutionary trends, and vulnerability of juniper formations in this coastal ecosystem. Bangladesh J. Bot. 54(3): 1045-1052, 2025 (September)